Qualitative Dissertation Methodology : A Guide for Research Design and Methods - Durdella, Nathan (Thousand Oaks Sage, 2019)
"It's no secret doctoral students struggle to write their dissertations, particularly the methodology chapter. Qualitative Dissertation Methodology: A Guide for Research Design and Methods, by Nathan Durdella, helps students construct a qualitative methodological framework for their research, write it up, and continue onto the rest of the dissertation with confidence. With a warm and supportive tone, the author walks students through the process of constructing this framework from the very start, from to choosing chairs and developing qualitative support networks, outlining the qualitative chapter and delving into the writing, and setting students up for further work on their dissertations" --
Part 1: Preparing for Methodological Work -- Working as a Qualitative Methodologist in Dissertation Contexts -- Understanding a Dissertation as Qualitative Methodology: A Section-by-Section Approach -- Part 2: Developing a Methodology Chapter -- Framing a Dissertation Study Through a Research Tradition -- Identifying a Research Setting and Exploring Research Contexts -- Working with Data Sources: Selecting Research Participants and Forming -- Research Samples -- Developing Data Collection Instruments and Describing Data Collection Procedures -- Articulating Data Analysis Procedures -- Adopting a Reflexive Practice with a Discussion of Researcher Roles -- Part 3: Transitioning to Work after a Methodology Chapter -- Protecting Human Research Participants in Qualitative Dissertation Methodology -- Writing Up and Presenting Results of Qualitative Data Analysis.
Includes bibliographical references and index.
Keywords: Dissertations, Academic -- Methodology; Qualitative research -- Methodology